Success Factors for Lean Six Sigma Implementation and Time Cost Trade off in High Rise Office Buildings to Improve Cost and Time Performance - Muh Nur; Albert Eddy Husin (Budapest International Research and Critics University, 2022)
A high-rise office building is a physical form of construction work that is integrated with its seat, partly or completely located above and/or in the ground and/or that is sailed as a place for humans to carry out their activities. This research was carried out with the aim of determining Cost and Time Performance in high-rise office buildings with the Implementation of Lean Six Sigma and time cost trade off. In project execution, scheduling and good quality play an important role in the timeliness, cost, and quality of project completion. Project delays often occur in the process of implementing construction projects. The quality is not good because it does not match the technical specifications. In the end there is a loss on a project. The results of the analysis study used